Hot Buttons and Time Sinks: The Effects of Electronic Communication During Nonwork Time on Emotions and Work-Nonwork Conflict - Butts, Marcus M.; Becker, William J.; Boswell, Wendy R. (Academy of Management Journal, 2015)
As advances in communication technologies have made organizations more easily connected to their workforce outside of normal work hours, there is increased concern that employees may experience heightened work-nonwork conflict when away from the office. The current study investigates the effects of electronic communication received during nonwork time using an experience sampling methodology to examine within-person relationships among elements of electronic communication (affective tone, time required), emotional responses (anger, happiness), and work-to-nonwork conflict in a sample of 341 working adults surveyed over a seven-day period. Hierarchical linear modeling results suggested that both affective tone and time required were associated with anger, but only affective tone was associated with happiness. Further, anger was associated with work-to-nonwork conflict and mediated the effects of affective tone and time required on work-to-nonwork conflict. Results also revealed cross-level moderating effects of abusive supervision and communication sender together, as well as segmentation preference. Implications of these findings for future theorizing and research on electronic communication during nonwork time are discussed.